Structural characterization of environmentally relevant ternary uranyl citrate complexes present in aqueous solutions and solid state materials. Issue 6 (5th November 2014) - Basile, Madeline; Unruh, Daniel K.; Flores, Erin; Johns, Adam; Forbes, Tori Z.
Abstract : Structural characterization of U(vi ) : (Al(iii ), Fe(iii )) : citrate complexes provides insight into the formation of polynuclear clusters present in environmentally-relevant aqueous solutions. Abstract : Organic acids are important metal chelators in environmental systems and tend to form soluble complexes in aqueous solutions, ultimately influencing the transport and bioavailability of contaminants in surface and subsurface waters. This is particularly true for the formation of uranyl citrate complexes, which have been utilized in advanced photo- and bioremediation strategies for soils contaminated with nuclear materials. Given the complexity of environmental systems, the formation of ternary or heterometallic uranyl species in aqueous solutions are also expected, particularly with Al(iii ) and Fe(iii ) cations. These ternary forms are reported to be more stable in aqueous solutions, potentially enhancing contaminant mobility and uptake by organisms, but the exact coordination geometries of these soluble molecular complexes have not been elucidated. To provide insight into the nature of these species, we have developed a series of geochemical model compounds ([(UO2 )2 Al2 (C6 H4 O7 )4 ] 6− (U2 Al2 ), [(UO2 )2 Fe2 (C6 H4 O7 )4 ] 6− (U2 Fe2 -1) and [(UO2 )2 Fe2 (C6 H4 O7 )4 (H2 O)2 ] 6− (U2 Fe2 -2 ) and [(UO2 )2 Fe4 (OH)4 (C6 H4 O7 )4 ] 8− (U2 Fe4 )) that were characterized by single-crystal X-ray diffraction and vibrational spectroscopy. Mass spectroscopy was then employed to compare the model compounds to species present in aqueous solutions to provide an enhanced understanding of the ternary uranyl citrate complexes that could be relevant in natural systems.